Behavioural avoidance by slugs and snails of the parasitic nematode Phasmarhabditis hermaphrodita. Issue 8 (2nd August 2016) - Wynne, R.; Morris, A.; Rae, R.
ABSTRACT: The nematode Phasmarhabditis hermaphrodita has been developed as a biological control agent for slugs and snails. Slugs avoid areas where P. hermaphrodita is present. We investigated whether behavioural avoidance of P. hermaphrodita is a common feature of slugs and snails by exposing eight species to P. hermaphrodita . We showed that slugs generally avoided P. hermaphrodita, whereas snails did not. We also showed that slugs specifically avoided the commercial strain and a natural isolate of P. hermaphrodita and were not deterred by other nematodes such as Steinernema kraussei or Turbatrix aceti . We also showed that slugs avoided the dauer stage of P. hermaphrodita and not mixed-stage cultures. Furthermore, slugs do not avoid dead P. hermaphrodita or exudates from live nematodes. Taken together, we have unravelled further factors that are essential for slugs to avoid P. hermaphrodita in soil, which could have important implications for the biological control of slugs and snails.